Drotrecogin alfa (activated) for adults with severe sepsis and a low risk of death - Abraham, Edward P.; Laterre, Pierre-François; Garg, Rekha; Levy, Howard; Talwar, Deepak; Trzaskoma, Benjamin L.; François, Bruno; Guy, Jeffrey S.; Brückmann, Martina; Rea-Neto, Álvaro; Rossaint, Rolf; Perrotin, Dominique; et al. (The New England journal of medicine, 2005)
Drotrecogin alfa (activated) is approved for use in patients with sepsis who are at high risk for death. This controlled trial found no benefit in patients at a low risk for death (relative risk of death with drotrecogin alfa, 1.08). The rate of serious bleeding was higher with drotrecogin alfa. Drotrecogin alfa should not be used in patients with sepsis who have a low risk of death, such as those with single-organ failure or an APACHE II score below 25.
Gesehen am 28.04.2022